Antioxidant Activity of Parijoto Fruit Extract at Various Temperature of Food Processing - Pertiwi, Rizki Bhakti; Hidayah, Isti Nurul; Andrianty, Deby; Hasbullah, Umar Hafidz Asy'ari (Jurnal Ilmu Pangan dan Hasil Pertanian, 2019)
Parijoto (Medinilla speciosa) is a tropical plant that is used as traditional medicine by the community. This fruit contains many bioactive compounds. This study aims to analyze the effect of food processing temperature on the total phenolic compounds and antioxidant activity in parijoto extract. Tests are carried out at temperatures of 10, 30, 60, 75 and 100 ÂºC. Total phenolic compounds were analyzed by Folin-Ciocalteu method. Antioxidant activity were analyzed by DPPH (1,1-Diphenil-2-pikrilhidrazil) radical scavenging method. The results showed that the increased processing temperature causes a decrease in total phenolic compounds. This causes antioxidant activity to decrease. Processing at low temperatures is able to maintain the content of phenol compounds (33.02 Î¼g/ml) and the greatest antioxidant activity.